2020
DOI: 10.1080/15374416.2020.1731819
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Attenuates the Prospective Links from Peer Victimization to Internalizing Symptoms during Middle Childhood

Abstract: Objective: Peer victimization has been shown to be a robust predictor of depressive and anxiety symptoms over time. Relatively little is known, however, regarding what protective factors may attenuate these associations and render youth more resilient to this interpersonal stressor. Therefore, the current study examined sadness and worry regulation as moderators of the prospective links from peer victimization to internalizing symptoms over a 1-year period.Method: Participants included 464 predominantly Caucas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
1
7
0
4
Order By: Relevance
“…That way, those who possess self-regulation and control skills choose adequate behavioral adjustment strategies, self-control the development of their working schedule looking to respond appropriately to their tasks to improve their performance [8,30]. The self-regulation general variable is present in the promotion of motivational-affective strategies [28,29]; the type of assumed learning scope [31][32][33]; achievement emotions [34,35]; coping strategies [36]; academic confidence and procrastination [37]. Contrary to selfregulation, when a dys-regulatory behavior as procrastination is present [26,27], people decide to postpone actions regardless of their adverse effects, increasing the perceived stress level, affecting important adjustment behaviors.…”
Section: Students' Factors Of Regulation: Self-regulation Procrastination and Academic Self-efficacymentioning
confidence: 99%
“…That way, those who possess self-regulation and control skills choose adequate behavioral adjustment strategies, self-control the development of their working schedule looking to respond appropriately to their tasks to improve their performance [8,30]. The self-regulation general variable is present in the promotion of motivational-affective strategies [28,29]; the type of assumed learning scope [31][32][33]; achievement emotions [34,35]; coping strategies [36]; academic confidence and procrastination [37]. Contrary to selfregulation, when a dys-regulatory behavior as procrastination is present [26,27], people decide to postpone actions regardless of their adverse effects, increasing the perceived stress level, affecting important adjustment behaviors.…”
Section: Students' Factors Of Regulation: Self-regulation Procrastination and Academic Self-efficacymentioning
confidence: 99%
“…Specifically, childhood depression, characterized by emotional and cognitive disturbances, has been associated with high clinical and school maladjustment, other internalizing problems (e.g., anxiety, low self‐esteem, and stress), externalizing problems (e.g., somatization, aggressiveness, inattention‐hyperactivity and agitation), and peer relationship difficulties (e.g., victimization, poor social skills, and withdrawal) (Garaigordobil, Bernarás, Jaureguizar, & Machimbarrena, 2017; Kochel, Ladd, & Rudolph, 2012; Vaillancourt, Brittain, McDougall, & Duku, 2013). Other studies have also found that emotion regulation may influence the inverse, for example, moderating the link from peer problems to depression (Cooley, Blossom, Tampke, & Fite, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…En esta línea, se han encontrado elevadas tasas de psicopatología en estos menores (Norredam et al, 2018;Oppedal y Idsoe, 2015), siendo los trastornos más frecuentes el trastorno de estrés postraumático, la ansiedad y la depresión, con una mayor prevalencia en menores refugiados que en población local de la misma edad (Brockie et al, 2015;Fazel et al, 2012;Hodes, 2019;Reed et al, 2012;Scoglio y Salhi, 2021). La pobre salud mental y el déficit en regulación emocional derivados de la exposición repetida a la violencia en etapas evolutivas tempranas constituyen un factor de riesgo para la futura victimización del niño o adolescente (Cooley et al, 2020), debido a la baja autoestima, la desesperanza aprendida y los esquemas cognitivos disfuncionales adquiridos (Finkelhor et al, 2011;Scoglio y Salhi, 2021), además de provocar reacciones emocionales desproporcionadamente intensas ante ciertos estímulos (McLaughlin et al, 2014). Como consecuencia, cabría esperar que la promoción de la salud mental actuase como factor protector ante la victimización; hipótesis que ha sido confirmada recientemente por Cooley et al (2020), quienes observaron que el adecuado desarrollo de habilidades de regulación emocional ejerce un efecto protector frente a los efectos de futuros episodios de victimización.…”
Section: Introductionunclassified
“…La pobre salud mental y el déficit en regulación emocional derivados de la exposición repetida a la violencia en etapas evolutivas tempranas constituyen un factor de riesgo para la futura victimización del niño o adolescente (Cooley et al, 2020), debido a la baja autoestima, la desesperanza aprendida y los esquemas cognitivos disfuncionales adquiridos (Finkelhor et al, 2011;Scoglio y Salhi, 2021), además de provocar reacciones emocionales desproporcionadamente intensas ante ciertos estímulos (McLaughlin et al, 2014). Como consecuencia, cabría esperar que la promoción de la salud mental actuase como factor protector ante la victimización; hipótesis que ha sido confirmada recientemente por Cooley et al (2020), quienes observaron que el adecuado desarrollo de habilidades de regulación emocional ejerce un efecto protector frente a los efectos de futuros episodios de victimización. Este efecto protector de la promoción de la salud mental ha sido también demostrado en relación con la victimización escolar y el fenómeno del bullying (Arslan y Allen, 2022;Simón-Saiz et al, 2019).…”
Section: Introductionunclassified